2007
DOI: 10.4028/www.scientific.net/kem.361-363.1351
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Phosphate Ceramic Blasting on Titanium Surface Improve Bone Ingrowth

Abstract: Surface roughness modulates the osseointegration of orthopaedic and dental titanium implants. High surface roughness is currently obtained by blasting of titanium implants with silica or aluminium abrasive particles. This process includes into the surface abrasive particles and may cause the release of cytotoxic silica or aluminium ions in the peri implant tissue. To overcome this drawback, we currently develop an innovative gridblasting process using Biphasic Calcium Phosphate (BCP) particles (RBBM Resorbable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Titanium and its alloys are the most common materials, comprising 70%–80% of all used materials [ 6 , 7 , 8 ]. Due to their excellent mechanical properties, corrosion resistance, and biocompatibility, these materials are used in load-bearing areas such as orthodontics, orthopedics, and gastroenterology as well as for cardiovascular and reconstructive purposes [ 5 , 6 , 9 , 10 , 11 , 12 ]. Furthermore, components made of titanium can be easily manufactured in various shapes and textures [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium and its alloys are the most common materials, comprising 70%–80% of all used materials [ 6 , 7 , 8 ]. Due to their excellent mechanical properties, corrosion resistance, and biocompatibility, these materials are used in load-bearing areas such as orthodontics, orthopedics, and gastroenterology as well as for cardiovascular and reconstructive purposes [ 5 , 6 , 9 , 10 , 11 , 12 ]. Furthermore, components made of titanium can be easily manufactured in various shapes and textures [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is very little trace of CaPO 4 on the Ti surface (chemical analysis of the blasted surface showed that less than 1% CaPO 4 remained over the entire surface), this value seems to be sufficient to improve biocompatibility. The blasting of metallic dental implants with biphasic HA + β-TCP bioceramic powder (BCP ® surface treatment) was also developed by Anthogyr (Sallanches, France) [668]. Both techniques produce a biocompatible rough surface free of contaminants, and guarantee fast and effective osseointegration.…”
Section: Blast Coatingmentioning
confidence: 99%
“…It is now possible to manufacture products made of a variety of different materials, such as ceramics, polymers, and metals. Titanium-based alloys are widely used in the field of medical implant production [ 1 ] due to their biocompatibility and good physical and mechanical properties [ 2 , 3 , 4 , 5 , 6 ]. The excellent biocompatibility of commercially pure titanium (c.p.…”
Section: Introductionmentioning
confidence: 99%